Pola dan Struktur Ruang kawasan Agropolitan dalam Perspektif Ekonomi Politik - Sudaryono, . (Journal of Regional and City Planning, 2004)
This paper aims at offering an approach in conceptualizing the agropolitan region by positioning the peasants at the centrum. Employing political economy perspectives it could be identified the pattern and structure of agropolitan space and therefore its classification and typology. Suggestions on regulation to support such concept are proposed.Keywords: ekonomi politik, agropolitan, struktur ruang